Pengaruh Self Assessment System, SP2DK, Surat Teguran, dan Surat Paksa Terhadap Penerimaan Pajak - Setyawati, Anjeli; Tannar, Oryza (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2024)
The aim of this research is to find out the influence of the self-assessment system, SP2DK, warning letters and forced letters on tax revenues. The population in this research is data from Individual Taxpayers and Corporate Taxpayers within the scope of KPP Pratama Surabaya Karangpilang for the 2020-2023 period. Sampling used a saturated sampling technique, that is, all members of the population were used as research samples. The data collection technique uses documentation techniques, namely by collecting data from KPP Pratama Surabaya Karangpilang during the 2020-2023 period for research purposes. The testing tool in this research uses the Partial Least Square (PLS) method with WarpPLS 8.0 software. The research results show that the self-assessment system and warning letters have no effect on tax revenues at KPP Pratama Surabaya Karangpilang. Meanwhile, the issuance of SP2DK and forced letters has an impact on tax revenues at KPP Pratama Surabaya Karangpilang.